Evaluation of Displaced Medial Epicondyle Fracture in Children Treated Operatively with K Wire - Yogi, Sushil; Shrestha, Dinesh Kumar; Shah, Aman (Journal of Nepalgunj Medical College, 2022)
Introduction: Medial epicondyle fractures of humerus are one of the common pediatric elbow injuries accounting for nearly 11% of the elbow injuries. This avulsion apophyseal fracture can lead to non-union and valgus instability. Thus, open reduction and internal fixation is helpful in maintaining union and a stable functioning elbow joint. Aims: To evaluate the outcome of operative management of displaced medial epicondyle fracture of humerus by open reduction and internal fixation with Kirschner wires using MAYO elbow scoring. Methods: This prospective observational study was conducted at the Department of Orthopedics of Nepalgunj Medical College and Teaching Hospital, Kohalpur from July 2020 to December 2021 in childrenbetween six to 16 years of age. All the patients in study were treated by open reduction and internal fixation with K wires. Mayo elbow performance score was used for evaluating functional outcome. Results: Thirty six patients were included with the mean age of 11.5 years (SD ± 2.5). Twenty five patients were males and 11 were females. Left side was found to be predominantly involved in 23 patients (66.6%). The mean duration of union was found to be 6.6 weeks (SD±0.6). Thirty four patients had excellent result in Mayo elbow performance score while two patients showed good result. The mean Mayo elbow performance score was 96.4 (SD± 3.9). Conclusion: Open reduction and internal fixation with K wires in this type of fracture had excellent to good results. The complications like nonunion and valgus instability are found to have fewer occurrences in children treated with operative means of treatment.